The origin of slow Alfvénic solar wind at solar minimum. Issue 1 (12th December 2019) - Stansby, D; Matteini, L; Horbury, T S; Perrone, D; D'Amicis, R; Berčič, L
ABSTRACT: Although the origins of slow solar wind are unclear, there is increasing evidence that at least some of it is released in a steady state on overexpanded coronal hole magnetic field lines. This type of slow wind has similar properties to the fast solar wind, including strongly Alfvénic fluctuations. In this study, a combination of proton, alpha particle, and electron measurements are used to investigate the kinetic properties of a single interval of slow Alfvénic wind at 0.35 au. It is shown that this slow Alfvénic interval is characterized by high alpha particle abundances, pronounced alpha–proton differential streaming, strong proton beams, and large alpha-to-proton temperature ratios. These are all features observed consistently in the fast solar wind, adding evidence that at least some Alfvénic slow solar wind also originates in coronal holes. Observed differences between speed, mass flux, and electron temperature between slow Alfvénic and fast winds are explained by differing magnetic field geometry in the lower corona.